Pengaruh Organisasi Mahasiswa terhadap Kemampuan Manajemen Konflik Mahasiswa PGSD FKIP UNRI - Nst, Muhammad Haekal Sachedina; Syahrilfuddin, Syahrilfuddin; Erlisnawati, Erlisnawati (Lembaga Yasin AlSys, 2023)
This research aims to determine the conflict management abilities of PGSD FKIP UNRI students who join the organization. When joining an organization, students will face many people with various characters to achieve the same goal. Therefore, various kinds of conflicts will arise that need to be faced and resolved by students who join the organization. Students' conflict management skills while in an organization can be a training ground for students to prepare for the world of work later. This research is qualitative research, which was conducted on 15 respondents using a questionnaire instrument. In its implementation, the questionnaire was distributed to students who were participating or had previously participated in the PGSD FKIP UNRI Study Program. All respondents answered questions online. The research results show that all respondents can be said to be good or indicated to be good in managing conflict according to the indicators used.